Understanding Suicide in Nepal from Socio-psychological Perspectives - Adhikari, Laxmi (Baneshwor Campus Journal of Academia, 2023)
The article explores on the theoretical and empirical evidences of growing suicide trend in Nepal from psychological perspective. Nepal has been witnessing the increasing suicidal attempts since the last two decades. The paper is developed based on the secondary sources of data. The published research papers, government information, suicide recorded information of police headquarter, governmental and non-governmental reports are the major sources of information. The study found that various socioeconomic, demographic, cultural, biological factors to mental illness such as anxiety, disorder and hopelessness are critical issues for suicide attempts in Nepal. It is argued that socio-environmental, cross-cultural, demographic factors have contributed to develop mental illness. If mental illness is not addressed timely then suicidal attempt is likely to happen. Government response to prevent suicidal attempt is not sufficient. Based on the second generation, theoretical understanding and prevention measures are crucial for the prevention.